2, 3, 7, 8‐Tetrachlorodibenzo‐p‐dioxin promotes endothelial cell apoptosis through activation of EP3/p38MAPK/Bcl‐2 pathway. Issue 12 (12th July 2017) - Yu, Yu; Liu, Qian; Guo, Shumin; Zhang, Qianqian; Tang, Juan; Liu, Guizhu; Kong, Deping; Li, Juanjuan; Yan, Shuai; Wang, Ruiguo; Wang, Peilong; Su, Xiaoou; et al.
Abstract: Endothelial injury or dysfunction is an early event in the pathogenesis of atherosclerosis. Epidemiological and animal studies have shown that 2, 3, 7, 8‐tetrachlorodibenzo‐ p ‐dioxin (TCDD) exposure increases morbidity and mortality from chronic cardiovascular diseases, including atherosclerosis. However, whether or how TCDD exposure causes endothelial injury or dysfunction remains largely unknown. Cultured human umbilical vein endothelial cells (HUVECs) were exposed to different doses of TCDD, and cell apoptosis was examined. We found that TCDD treatment increased caspase 3 activity and apoptosis in HUVECs in a dose‐dependent manner, at doses from 10 to 40 nM. TCDD increased cyclooxygenase enzymes (COX)‐2 expression and its downstream prostaglandin (PG) production (mainly PGE2 and 6‐keto‐PGF1α ) in HUVECs. Interestingly, inhibition of COX‐2, but not COX‐1, markedly attenuated TCDD‐triggered apoptosis in HUVECs. Pharmacological inhibition or gene silencing of the PGE2 receptor subtype 3 (EP3) suppressed the augmented apoptosis in TCDD‐treated HUVECs. Activation of the EP3 receptor enhanced p38 MAPK phosphorylation and decreased Bcl‐2 expression following TCDD treatment. Both p38 MAPK suppression and Bcl‐2 overexpression attenuated the apoptosis in TCDD‐treated HUVECs. TCDD increased EP3‐dependent Rho activity and subsequently promoted p38MAPK/Bcl‐2 pathway‐mediated apoptosis in HUVECs. In addition, TCDD promoted apoptosis in vascular endothelium and delayed re‐endothelialization after femoral artery injury in wild‐type (WT) mice, but not in EP3 −/− mice. In summary, TCDD promotes endothelial apoptosis through the COX‐2/PGE2 /EP3/p38MAPK/Bcl‐2 pathway. Given the cardiovascular hazard of a COX‐2 inhibitor, our findings indicate that the EP3 receptor and its downstream pathways may be potential targets for prevention of TCDD‐associated cardiovascular diseases.